Energy Thermodynamics Revisited: Energy intake strategies for optimizing athlete body composition and performance - Benardot, Dan (2013)
A key feature of physical activity is that it results in an increased rate of energy expenditure and, as a result of metabolic inefficiencies that lead to high heat production, an increase in the requirement to dissipate the added heat through sweat.  Nevertheless, surveys commonly find that athletes fail to optimally satisfy both energy and fluid needs, causing them to perform at levels below their conditioned capacities.  To some extent this problem results from an excess reliance on the sensations of ‘hunger’ and ‘thirst’ to guide energy and fluid intakes, but there are also common misunderstandings of the best eating strategies for achieving optimal body composition and performance.  The need to improve the strength-to-weight ratio to enable an enhanced ability to overcome sport-related resistance can be misinterpreted as a need to be ‘small’, which may result in an under-consumption of energy through restrained eating and special ‘diets’.  The outcome, however, is nearly always the precise opposite of the desired effect, with lower strength-to-weight ratios that result in an ever-increasing downward spiral in energy and fluid consumption.  This paper focuses on within-day energy balance eating and drinking strategies that are now successfully followed by many elite-level athletes.  These strategies can help athletes avoid the common errors of under-consumption while simultaneously improving both body composition and performance.